The Role of Al-Jailaini’s Hagiography among Javanese Muslims in Yogyakarta - Munip, Abdul (el Harakah: Jurnal Budaya Islam, 2018)
The Islamic rituals in Indonesia have been studied from several perspectives by many scholars. The rituals are usually performed by using several tools, and the text is most used and read in every ritual. However, the studies do not explain the text used in the rituals comprehensively. Therefore, this paper is meant to describe the roles or functions of the text used in the manaqiban ritual performed by Jamaah Aolia Gunung Kidul Yogyakarta. Using a qualitative method based on participate observations and in-depth interviews, the study finds that an-Nur al-burhani, a Javanese translation of al-Jailani ’s hagiography, is the crucial tool in the ritual. The text is merely a historical book about the miracles of al-Jailani , but it has been sacred and transformed with several functions. First, the text serves as a manual for performing the manaqiban. Second, the text as a sacred mantra must be read in the ritual. Third, the text can serve as a consolation for the participants. Fourth, the text serves as a binder for internal group solidarity. Fifth, the text as a source of educational values. Ritual Islam di Indonesia telah diteliti dari beberapa perspektif oleh para ilmuwan. Biasanya, ritual dilakukan dengan menggunakan beberapa sarana, dan teks adalah sarana yang paling digunakan dan dibaca dalam setiap ritual. Namun demikian, beberapa hasil penelitian tersebut tidak menjelaskan teks yang digunakan dalam ritual secara komprehensif. Oleh karena itu, artikel ini dimaksudkan untuk menggambarkan peran dan fungsi teks dalam ritual manaqiban yang diselenggarakan oleh Jamaah Aolia Gunung Kidul Yogyakarta. Dengan menggunakan pengamatan partisipatif dan wawancara mendalam, penelitian ini menemukan bahwa an-Nur al-burhani, sebuah buku terjemahan berbahasa Jawa dari hagiografi al-Jailani, adalah sarana terpenting dalam ritual. Teks buku ini pada dasarnya hanyalah narasi tentang karamah al-Jailani, namun telah diskralkan sehingga memiliki beberapa fungsi. Pertama, teks sebagai manual dalam pelaksanaan manaqiban. Kedua, teks sebagai sebuah mantra sakral yang harus dibaca dalam ritual. Ketiga, teks dapat berfungsi sebagai hiburan bagi para peserta. Keempat, teks berfungsi sebagai pengikat solidaritas internal. Kelima, teks sebagai sumber nilai pendidikan.